Farm‐derived Gram‐positive bacterium Staphylococcus sciuri W620 prevents asthma phenotype in HDM‐ and OVA‐exposed mice. Issue 3 (1st February 2013) - Hagner, S.; Harb, H.; Zhao, M.; Stein, K.; Holst, O.; Ege, M. J.; Mayer, M.; Matthes, J.; Bauer, J.; von, E.; Renz, H.; Heine, H.; et al.
Abstract Background Farm‐derived dust samples have been screened for bacteria with potential allergo‐protective properties. Among those was Staphylococcus sciuri W620 (S. sciuri W620), which we tested with regard to its protective capacities in murine models of allergic airway inflammation. Methods We employed two protocols of acute airway inflammation in mice administering either ovalbumin (OVA) or house dust mite extract (HDM) for sensitization. Mechanistic studies on the activation of innate immune responses to S. sciuri W620 were carried out using human primary monocytic dendritic cells (moDC) and co‐culture with autologous T cells. Results The allergo‐protective properties of S. sciuri W620 were proven in a TH2‐driven OVA model as well as in a mixed TH1/TH2 phenotype HDM model as demonstrated by abrogation of eosinophils and neutrophils in the airways after intranasal treatment. In the HDM model, lymph node cell TH1/TH2 signature cytokines were decreased in parallel. Studies on human moDC revealed an activation of TLR2 and NOD2 receptors and initiation of DC maturation following incubation with S. sciuri W620. Cytokine expression analyses after exposure to S. sciuri W620 showed a lack of IL‐12 production in moDC due to missing transcription of the IL‐12p35 mRNA. However, such DC selectively supported TH1 cytokine release by co‐cultured T cells. Conclusion and clinical relevance Our proof‐of‐concept experiments verify the screening system of farm‐derived dust samples as suitable to elucidate new candidates for allergo‐protection. S. sciuri W620 was shown to possess preventive properties on airway inflammation providing the basis for further mechanistic studies and potential clinical implication.